Effects of extraction period on yield of rice straw compost humic acids - Perumal, Palanivell; Kasim, Susilawati; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Academic Journals, 2012)
Humic acids (HA) are widely used in agriculture because of their capability as chelator, organic matter, soil improver and growth promoter. However, their isolation differs in terms of origin or source because of wetting and solubilization factors. This study was conducted to determine extraction period for HA from composted rice straw. Standard procedures were used to extract HA from rice straw compost at different extraction periods of 4, 8, 12, 16, 20 and 24 h. At the end of each extraction period, samples were centrifuged, followed by fractionation and purification. HA yield at different extraction periods was determined and the HA samples were analyzed using standard procedures. The relationship between extraction period and rice straw compost HA yield was quadratic. Extraction period for rice straw compost was 21.6 h and purification (done within 1 h) using distilled water was effective in removing impurities. Moreover, the HA produced at different extraction periods were similar in terms of chemical and spectral characteristics. HA from rice straw compost can be extracted within 24 h and purification can be done in relatively short time without changing their chemical and spectral properties to produce K-humate.